Deformation microstructures in zircon and monazite: implications for shock, tectonic and geochronological studies - Erickson, Timmons Manning (Curtin University, 2016)
Zircon and monazite have been studied by quantitative microstructural analysis to constrain deformation processes in both tectonic and shock environments. Results provide new constraints on twinning, shock transformation to high pressure polymorphs and the conditions of formation of impact microstructures. Trace element mobility and modification of U – Pb ages, linked to crystal-plastic deformation in these environments, provides new strategies for dating the timing of deformation events by in situ analyses of microstructurally characterized accessory phases.